O princípio da legalidade e o direito penal econômico: análise sob a perspectiva do Estado Democrático de Direito - Gustavo Henrique de Souza e Silva (2011)
The principle of legality is the cornerstone of the entire conception of the model of a democratic state. Through its formal and material conceptions, the model adopted by the Constitution subjects the state authority to the precepts and individual rights to promote human dignity, avoid the arbitrariness of those in power, and build a free and just society. As a result, the criminal policy consecrated by the Constitution is theminimum of a criminal law whose legitimacy requires the description of detrimental or concretely dangerous behaviors to legal property, here understood as those prelegal, constitutionalized values whose conveyance to the sphere of the individual, even when considered collectively, is necessary. The recognition of legality also implies, in terms of its function in written law, the removal of criminalization of customs set out by the previous law, removing the retroactivity of tort brought to the defendant involving strict law, averting the in malam partem analogy, and the broad interpretation of the incriminating norms and stringent law, imposing upon the lawmakers the duty to draft legal, clear, and specific precepts. Such guarantees cannot be relativized, even under the guise of a supposedly more efficient policy on crime to fight an alleged new crime, characterized by supra-individual legal intangibilities. Thus, also within the so-called economic criminal law, the issue of penal types of abstract danger, mere conduct, or indeterminate or any merely preventive or symbolic preventive intervention will be set aside. The separated types of these precepts should be interpreted as the fundamental law or have heir invalidity recognized by constitutional habit. Recognizing the ineptitude of criminal law to regulate certain circumstances relating to economic activities, we suggest alternative models that allow legitimate state intervention without sacrificing individual rights and guarantees